Comparison of Neutralizing Sars Cov-2 Igg Antibody Levels in Hospitalized Patients at Dr. Mohammad Hoesin Palembang Hospital - Zen Ahmad; Sudarto Sudarto; Ra Linda; Rouly PP; Alif FR; Syafran Rasyidi; Phey Liana (Malahayati Nursing Journal, 2023)
ABSTRACT COVID-19 is an acute respiratory disease that spreads rapidly throughout the world caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). Published research on levels of SARS-CoV-2 antibodies in hospitalized COVID-19 patients is still limited. Research on sero-epidemiology and its correlation with the clinical severity of COVID-19 is needed as a database for pandemic governance, especially research on neutralizing antibodies. This study was designed to compare the levels of IgG SARS CoV-2 on the tenth day in hospitalized patients with various clinical severity at RSUP Dr. Mohammad Hoesin Palembang. This research is an observational-analytic study with a cross-sectional design. The study was conducted in the COVID-19 isolation ward of RSMH Palembang from December 2021 to March 2022. IgG SARS CoV-2 level was measured in patients with confirmed COVID-19. Differences in IgG values of SARS CoV-2 were tested with the Mann Whitney test. The effect of various confounding variables in this study was tested using bivariate and multivariate tests in the form of a chi-square test and multiple linear regression on the scale of the dependent variable. The study included 50 patients, consisting of 22 patients with mild-moderate severity and 28 patients with severely-critically ill. Bivariate analysis showed there was no significant difference of IgG SARS-CoV-2 between two groups. From the data analysis using the ROC curve, the cut-off point for SARS-CoV-2 IgG levels in predicting the severity of COVID-19 disease was 500 AU/mL. IgG SARS-CoV-2 level of more than 500 AU/mL causes an increased risk of 3.69 (95% CI 1.13-11.98) times to suffer from severe-critical COVID-19. Serum IgG SARS-CoV-2 levels were found to be significantly higher in patients with severe-critical symptoms than patients with mild-moderate symptoms in COVID-19 hospitalized patients at Dr. Mohammad Hoesin Palembang hospital. Keywords: COVID-19, severity of COVID-19, IgG SARS-CoV-2